MARK inhibitors: Declaring a No-Go decision on a chemical series based on extensive DMPK experimentation. Issue 1 (1st January 2017) - Haidle, Andrew M.; Childers, Kaleen K.; Zabierek, Anna A.; Katz, Jason D.; Jewell, James P.; Hou, Yongquan; Altman, Michael D.; Szewczak, Alexander; Chen, Dapeng; Harsch, Andreas; Hayashi, Mansuo; Warren, Lee; et al.
Graphical abstract: Abstract: Attempts to optimize pharmacokinetic properties in a promising series of pyrrolopyrimidinone MARK inhibitors for the treatment of Alzheimer's disease are described. A focus on physical properties and ligand efficiency while prosecuting this series afforded key tool compounds that revealed a large discrepancy in the rat in vitro–in vivo DMPK (Drug Metabolism/Pharmacokinetics) correlation. These differences prompted an in vivo rat disposition study employing a radiolabeled representative of the series, and the results from this experiment justified the termination of any further optimization efforts.